The Analysis of Labor Law Arrangements against Women Workers - Audrine Gandhis Arsita Dini; Nabitatus Sa'adah (Universitas Islam Sultan Agung, 2023)
This article aims to identify and analyze labor law arrangements for women workers (Case Study of PT KEM). PT Kelian Equatorial Mining (KEM) is engaged in mining and metals. PT Kelian Equatorial Mining (KEM) has been established in Indonesia since 1992 located in West Kutai Regency, East Kalimantan Province. PT KEM obtained a Contract of Work from the government in 1985, then began mining for gold in 1992 and closed production in 2005 due to running out of mining products. This legal research uses a normative method which is carried out by means of literature study on secondary data. The results of this study indicate that there are several sources of law, both national and international, that protect women workers, including Act No. 13 of 2003 concerning Manpower. However, it is undeniable that violence, discrimination and sexual harassment against women in the workplace continue to occur. The government, law enforcers and companies need to pay attention to how to enforce the laws governing women workers, and make it easier to access reports of incidents related to violations of their rights at companies. In this way, the rights of women workers will be protected from any actions that harm them in relation to the work they do at the company.